Solve the following system of equations for all three variables
6x + 8y - 3z = -10
2x + 8y - 5z = 2
-5x - 8y + 4z = 7
We can eliminate y by subtracting the first and second equations and add the second and third equations.
So we have two equations and two variables now:
Now we can use the elimination method to eliminate z by multiplying the bottom equation by 2 and adding it with the bottom.
so now we know z=0 by substituting x into the previous equation.
similarly, we can find that y=1 by substituting x and z into any of the orig equations
Hope this helps